2020
DOI: 10.1177/0885066620973585
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Clinical and Scientific Rationale for the “MATH+” Hospital Treatment Protocol for COVID-19

Abstract: In December 2019, COVID-19, a severe respiratory illness caused by the new coronavirus SARS-CoV-2 (COVID-19) emerged in Wuhan, China. The greatest impact that COVID-19 had was on intensive care units (ICUs), given that approximately 20% of hospitalized cases developed acute respiratory failure (ARF) requiring ICU admission. Based on the assumption that COVID-19 represented a viral pneumonia and no anti-coronaviral therapy existed, nearly all national and international health care societies’ recommended “suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 195 publications
(355 reference statements)
0
26
0
1
Order By: Relevance
“…The Front Line COVID-19 Critical Care Alliance (FLCCC), a clinical expert panel, developed a treatment protocol based on the core therapies methylprednisolone, ascorbic acid, thiamine, heparin, and co-interventions (MATH+) for hospitalized patients [78]. Recently, ivermectin, an anti-parasitic medicine with potent anti-viral and anti-inflammatory properties against COVID-19 was added to the list.…”
Section: Acute Respiratory Distress Syndrome (Ards)mentioning
confidence: 99%
“…The Front Line COVID-19 Critical Care Alliance (FLCCC), a clinical expert panel, developed a treatment protocol based on the core therapies methylprednisolone, ascorbic acid, thiamine, heparin, and co-interventions (MATH+) for hospitalized patients [78]. Recently, ivermectin, an anti-parasitic medicine with potent anti-viral and anti-inflammatory properties against COVID-19 was added to the list.…”
Section: Acute Respiratory Distress Syndrome (Ards)mentioning
confidence: 99%
“… 17 The medication has been highly publicized as useful and effective in prevention and treatment of COVID-19 by the group Front Line COVID-19 Critical Care Alliance. 18 However, a recent double-blind randomized trial including 478 patients showed no significant difference in time to resolution of symptoms in the ivermectin group vs placebo. 19 A few small trials in the United States and Europe compared ivermectin plus doxycycline to “standard” care.…”
Section: Evidence-based Outpatient Therapeuticsmentioning
confidence: 97%
“…[ 27 31 97 98 99 100 101 102 103 104 ] The studies conducted so far on the clinical utility of IVM as therapeutic as well as prophylactic regimen are given in Table 3 . [ 31 68 69 70 71 72 73 105 106 107 108 109 110 111 112 113 114 115 ]…”
Section: Covid-19mentioning
confidence: 99%